Influence of novel readthrough agents on myelin protein zero translation in the peripheral nervous system. (15th June 2022) - Otani, Yoshinori; Taguchi, Akihiro; Hamada, Keisuke; Hayashi, Yoshio; Yamaguchi, Yoshihide; Baba, Hiroko
Abstract: Translational readthrough-inducing agents have been developed for the treatment of nonsense mutations in hereditary diseases. The clinical effectiveness of readthrough agents has been reported, although newly developed agents are still desired because of their toxicities or limited clinical effectiveness. Recently, novel negamycin-derived readthrough agents without antimicrobial activity have been developed. Our aim was to evaluate the activities of these readthrough agents by monitoring the production of large myelin protein zero (L-MPZ), the programmed translational readthrough isoform of myelin protein zero (P0, MPZ) mRNA, and to clarify the influence of these agents on the sciatic nerve in vivo . First, we examined the readthrough activities of novel negamycin-derived agents using cell-free and cell culture systems using plasmids encoding human MPZ (hP0) cDNA. Three of the negamycin derivatives, TCP-112, TCP-169, and TCP-1109, suppressed the canonical stop codon to induce readthrough. Direct injection of TCP-1109, which showed higher readthrough activity for Mpz in mouse sciatic nerves, exhibited a 1.3-fold increase in the L-MPZ/P0 ratio compared to that with the vehicle control on western blotting. The nerve conduction velocity and beam walk test showed abnormalities in the classical readthrough agent G418-treated group, but not in the TCP-1109-treated group. Immunofluorescence analysis showed that TCP-1109 caused less damage to the sciatic nerve than G418. In the semi-thin sections, a lower g-ratio and more tomacula-like structures were observed in TCP-1109-treated nerves. Thus, the present results indicate that negamycin-derived readthrough agents enhance programmed translational readthrough, and the management of readthrough activities using canonical stop codons may be important. Highlights: A novel negamycin-derived readthrough agent (TCP-1109) increased the production of the readthrough isoform L-MPZ both in vitro and in vivo. Direct injection of TCP-1109 caused less damage to the sciatic nerve and no apparent impairment of motor function, in contrast to G418. Understanding the influence of readthrough drugs on programmed readthroughs is important for clinical use.